Is the Euro-zone on the Mend? Latin American examples to analyze the Euro question - Cavallo, Eduardo A.; Fernández-Arias, Eduardo; Powell, Andrew (Journal of Banking & Finance, 2014)
Several European countries face challenges reminiscent of those faced by the emerging economies of Latin America. The economic booms in some peripheral Euro-zone countries financed by large capital inflows; the credit and asset price booms and then the busts including Sudden Stops in capital flows; the strong interaction between sovereign debt and domestic banking systems; the role of foreign banks and contagion; and all in the context of a fixed exchange rate, are familiar plotlines for Latin American audiences. For those Euro-zone countries that built up large Euro-denominated external liabilities, Latin America’s experience is particularly relevant and worrisome. Still, Europe may be in a better position to navigate a path out of the crisis given cooperative mechanisms that were absent in Latin America, particularly the availability of massive liquidity support. Nonetheless, while such support buys time, it does not guarantee success. This paper argues that reflecting on Latin America’s experience provides useful lessons for Europe to improve the chances for a successful resolution.